The Role Of The Religious Laboratory In Improving Students 'Understanding Of Fiqh Lessons - Siti Na’ilul Hidayah; Ashif Az-zafi (Pascasarjana Pendidikan Agama Islam Institut KH. Abdul Chalim Mojokerto, 2021)
This study aims to determine and describe the role of religious laboratory media in improving students' understanding of the Fiqh subject. This study uses a descriptive qualitative approach and uses the method of interviewing, observing, and documenting. Meanwhile, the subjects of this study were teachers, students, and all parties involved with the religious laboratory of MA Tarbiyatul Banin Winong Pati. From this research, it can be concluded that the use of religious laboratory media can improve students' understanding of the subject of Fiqh. By using this security laboratory, media allows students to understand directly the material explained and allows more effective learning.